2009
DOI: 10.1007/s00259-009-1119-8
|View full text |Cite
|
Sign up to set email alerts
|

188Re-HEDP combined with capecitabine in hormone-refractory prostate cancer patients with bone metastases: a phase I safety and toxicity study

Abstract: Purpose188Re-HEDP is indicated for the treatment of pain in patients with painful osteoblastic bone metastases, including hormone-refractory prostate cancer patients. Efficacy may be improved by adding chemotherapy to the treatment regimen as a radiation sensitizer. The combination of 188Re-HEDP and capecitabine (Xeloda®) was tested in a clinical phase I study.MethodsPatients with hormone-refractory prostate cancer were treated with capecitabine for 14 days (oral twice daily in a dose escalation regimen with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…The toxicity did not correlate with the response of pain [125]. 89 Sr demonstrate similar toxicity as the other common radiopharmaceuticals, such as 186 Re-HEDP, 188 Re-HEDP, and 153 Sm-EDTMP [127].…”
Section: Strontiummentioning
confidence: 63%
See 4 more Smart Citations
“…The toxicity did not correlate with the response of pain [125]. 89 Sr demonstrate similar toxicity as the other common radiopharmaceuticals, such as 186 Re-HEDP, 188 Re-HEDP, and 153 Sm-EDTMP [127].…”
Section: Strontiummentioning
confidence: 63%
“…Sm-EDTMP 233 Ra 186 Re-HEDP 188 Re-HEDP 117m Tin-DTPA a b s t r a c t Internal radiotherapy is effective in the treatment of metastatic bone pain and can improve quality of life. A number of controlled studies using various agents have shown a mean response rate in pain relief of 70-80% of treated patients.…”
Section: Srmentioning
confidence: 99%
See 3 more Smart Citations